Reducing Superfluous Opioid Prescribing Practices After Brain Surgery: It Is Time to Talk About Drugs. (18th December 2021) - Asmaro, Karam; Fadel, Hassan A; Haider, Sameah A; Pawloski, Jacob; Telemi, Edvin; Mansour, Tarek R; Chandra, Ankush; Bazydlo, Michael; Robin, Adam M; Lee, Ian Y; Air, Ellen L; Rock, Jack P; et al.
Graphical Abstract: